EFFECT OF EXTRACTION METHODS ON TOTAL FLAVONOID CONTENT AND ANTIOXIDANT ACTIVITY POTENTIAL OF ETHANOL EXTRACT OF GALING-GALING LEAVES (Cayratia trifolia (L.) Domin) - I Kadek Suardiana; A.A. Gede Rai Yadnya Putra; Pande Made Nova Armita Sari (Pharmacy Department, Math and Sciences Faculty, Udayana Univerity, 2025)
Background: Antioxidants play a key role in the prevention and treatment of various diseases. Flavonoids, a class of secondary metabolites, are known for their strong antioxidant properties. Cayratia trifolia (L.) Domin is an Indonesian endemic plant with medicinal potential, particularly as a natural antioxidant source. The extraction process is a critical step in isolating bioactive compounds and must be optimized to maximize flavonoid content and antioxidant activity. Objective: This study aims to evaluate the effect of different extraction methods— maceration, sonication, and Soxhlet extraction—on the total flavonoid content and antioxidant activity of ethanolic extracts of C. trifolia (L.) Domin leaves. Methods: This experimental study used three extraction techniques: maceration, sonication, and Soxhlet extraction. Total flavonoid content was determined using UV-Vis spectrophotometry and expressed as mg quercetin equivalent per gram of extract (mg QE/g extract). Antioxidant activity was measured using the DPPH free radical scavenging assay and expressed as IC₅₀ (ppm). Statistical analysis was conducted using one-way ANOVA with a 95% confidence level. Results: The sonication method yielded the highest total flavonoid content (41.82 ± 0.011 mg QE/g extract) and the strongest antioxidant activity (IC₅₀ = 66.523 ± 0.449 ppm), followed by Soxhlet extraction (35.78 ± 0.01 mg QE/g; IC₅₀ = 84.217 ± 0.565 ppm), and maceration (18.48 ± 0.01 mg QE/g; IC₅₀ = 94.579 ± 1.12 ppm). Statistical analysis showed that the extraction method significantly affected both total flavonoid content and antioxidant activity (P < 0.05). Conclusion: The extraction method significantly influences the yield of total flavonoids and antioxidant activity in C. trifolia ethanolic leaf extracts. Sonication was found to be the most effective method, suggesting its potential use in optimizing the recovery of antioxidant compounds from plant materials. Keywords: Antioxidant Activity; Cayratia trifolia (L.) Domin; DPPH; Extraction methods; Total Flavonoid Contents.